Great writing 1 : - Folse, Keith S. (Heinle Cengage Learning, 2010)
The Great Writing series uses clear explanations and extensive practical activities to help students write great sentences, paragraphs, and essays. Each book contains a wide variety of writing models in carefully selected rhetorical styles that provide practice in working with the writing process to develop a final piece of writing. In Great Writing 1: Great Sentences for Great Paragraphs, basic writing skills are built by focusing on the elements of a good sentence within the context of a paragraph.